TILRR Aggravates Sepsis-Induced Acute Lung Injury by Suppressing the PI3K/Akt Pathway. (26th August 2022) - Wang, Xiaoyu; Lin, Feixue; Guo, Lisha
Abstract : Acute lung injury (ALI) is a life-threatening lung change, and 40% of ALI cases result from sepsis. However, the effective treatment for sepsis-induced ALI is limited. It is urgent to explore novel therapeutic targets for ALI caused by sepsis. Anti-inflammatory therapy is a potential effective treatment for sepsis-induced ALI. Toll-like/Interleukin-1 receptor regulator (TILRR) could trigger aberrant inflammatory responses. Nevertheless, the role of TILRR in sepsis-induced ALI remains unknown. Besides, the phosphatidylinositol 3′kinase/protein kinase B (PI3K/Akt) pathway exerts protective effect on sepsis-induced ALI. Thus, the primary aim of the current study was to investigate whether TILRR contributed to sepsis-induced ALI by the PI3K/Akt pathway. To construct the sepsis-induced ALI model, human pulmonary microvascular endothelial cells (HPMVECs) were treated with lipopolysaccharide (LPS). Besides, the mRNA levels and protein levels were determined by quantitative reverse transcription-PCR (qPCR) and Western blot (WB), respectively. Moreover, cell proliferation was identified by the Cell Counting Kit-8 (CCK-8) assay and Annexin V was utilized to detect apoptosis. Furthermore, levels of proinflammatory cytokines and oxidative stress were tested by the enzyme-linked immunosorbent assay (ELISA) while reactive oxygen species (ROS) was determined by the flow cytometer. Results indicated that TILRR was upregulated to suppress the proliferation and induce apoptosis of HPMVECs under LPS treatment. Besides, TILRR induced aberrant inflammatory responses and oxidative stress in HPMVECs under LPS treatment. Mechanistically, TILRR regulated proliferation, apoptosis, inflammatory responses, and oxidative stress in LPS-treated HPMVECs through inactivating the PI3K/Akt pathway. In summary, TILRR aggravated sepsis-induced ALI by suppressing the PI3K/Akt pathway. These results could provide novel therapy targets for sepsis-induced ALI.